Convergence of TTS Iterative Method for Non-Hermitian Positive Definite Linear Systems - Cheng-Yi Zhang (Mathematical Problems in Engineering, 2014)
The TTS iterative method is proposed to solve non-Hermitian positive definite linear systems and some convergence conditions are presented. Subsequently, these convergence conditions are applied to the ALUS method proposed by Xiang et al. in 2012 and comparison of some convergence theorems is made. Furthermore, an example is given to demonstrate the results obtained in this paper.